Computational drug design of potential α-amylase inhibitors using some commercially available flavonoids (Bangladesh Journal of Pharmacology, 2014)
The primary objective of this study was to investigate the α-amylase inhibitory activity of flavonoids using in silico docking studies. In this perspective, flavonoids like biochanin, chrysin, hesperitin, morin, tricin and vitexycarpin were selected. Acarbose, a known α-amylase inhibitor was used as the standard. In silico docking studies were carried out using AutoDock 4.2, based on the Lamarckian genetic algorithm principle. The results showed that all the selected flavonoids showed binding energy ranging between -7.20 kcal/mol to -6.21 kcal/mol when compared with that of the standard (-2.94 kcal/mol). Inhibition constant (5.31 µM to 27.89 µM) and intermolecular energy (-8.99 kcal/mol to -7.41 kcal/mol) of the flavonoids also coincide with the binding energy. The α-amylase inhibitory activity of the selected flavonoids was in order of tricin > hesperitin > vitexycarpin > chrysin > morin > biochanin. These molecular docking analyses could lead to the further development of potent α-amylase inhibitors for the treatment of diabetes.